The Impact of PLN Mobile’s Meter Recording Feature Implementation on Customer Satisfaction in Postpaid Electricity Services - Maulana Gilang Syahdat; Fahrul Riza; Yuli Kartika Dewi (Publikasi Indonesia, 2026)
This study examines the impact of the Meter Reading feature in the PLN Mobile application on customer satisfaction by employing the Technology Acceptance Model (TAM) integrated with TRUST as a mediating variable. A total of 102 active postpaid customers participated in an online survey using a 5-point Likert scale. Data were analysed using PLS-SEM through validity, reliability, discriminant, and bootstrapping tests. The findings reveal that Perceived Ease of Use (PEOU) significantly influences both Perceived Usefulness (PU) and Customer Satisfaction (CS), making it the most dominant driver of user experience. PU also demonstrates a significant effect on CS and strongly predicts TRUST, showing that perceived benefits strengthen confidence in system reliability. TRUST significantly contributes to CS and serves as a partial mediator in the relationship between PU and CS. These results extend TAM by confirming the strategic role of TRUST within mandatory public utility services. Practically, the study highlights the importance of enhancing usability, functional benefits, and perceived system integrity to improve customer satisfaction with PLN Mobile.